Pierre Elliott Trudeau and Bill C-150: A rational approach to homosexual acts, 1967--1969 - Chambers, Stuart (University of Ottawa (Canada), 2003)
The following thesis outlines the historical significance of Bill C-150, the Omnibus Criminal Code Reform Bill. From 1967--69, Canadian law was forever changed when the "omnibus bill," formerly known as Bill C-195, was introduced in December of 1967. The Justice Minister at the time, Pierre Elliott Trudeau, was attempting to modernize the Criminal Code of Canada, but his first attempt---Bill C-195---died on the Order Paper during the 1967--68 Session (the 2nd Session of the 27th Parliament). Reintroduced in December of 1968 (the 1st session of the 28th Parliament), the newly revamped Bill C-150 contained many of the same traits as its predecessor. This time, however, Trudeau had taken over as Prime Minister from Lester B. Pearson and was confident in the new mandate given to him by the Canadian electorate. As a result, he appointed John Napier Turner as his new Justice Minister. Therefore, what Trudeau and the Liberals were proposing was the modernization of the country's family law. For the purposes of this thesis, the focus will deal strictly with the controversy surrounding the Canadian Criminal Code's liberalization of homosexual acts between consenting adults in private. (Abstract shortened by UMI.)
Keywords: History, Canadian.; Law.